Ictioplancton en la zona portuaria de Limón, Costa Rica - Dominici-Arosemena, Arturo; Brugnoli-Olivera, Ernesto; Solano-Ulate, Sylvia; Molina-Ureña, Helena; Ramírez Coghi, Ana Rosa (Revista de Biología Tropical, 2000)
Four sampling stations were set 200-500m off Limon Port, Costa Rica, at an average depth of 20 m. From October 1996 to May 1997 horizontal subsuperficial trawls were done for 12 minutes at a speed of about 2KmIh, with a 1 OOO¡.tm plancton neto A total of 28 samples were processed and 104 physieal-chemistry parameter measurements were taken. Average salinity was 30.1 ± 3.7 and dissolved oxygen 6.9 ± 0.6 mg 1-1 reflecting good aeration throughout the sampling périod. This suggests good mixture and a highly dynamic hydrography. Temperature showed no drastic variations (28.0 ± 1.7 OC), possibly because of the constant mixing with shallow water. The highest larval counts were for November and early January and inelude families common to reefs and estuaries (BaJistidae, Lutjanidae) and to coastal areas (Centropomidae, Gerreidae, Haemulidae, Carangidae, Engraulidae, Hemiramphidae, and representative Pleuronectiforrnes) existing in a common area.